Facilitating with Ease! Core Skills for Facilitators, Team Leaders and Members, Managers, Consultants, and Trainers. - Bens, Ingrid (John Wiley & Sons, 2012)
Since the publication of the first edition of Facilitating with Ease! in 2000, this bestselling book has become the "go-to" reference for anyone who wants to become skilled in the art of facilitation. This thoroughly revised and updated third edition includes easy-to-follow instructions, techniques, and hands-on tools. Facilitating with Ease! offers the basics on running productive meetings with confidence and includes the information needed to train others to become skilled facilitators as well. Filled with dozens of exercises, surveys, and checklists that can be used to transform anyone into an effective facilitator, this revised editioncovers new topics such as: Why and when leaders should facilitate and how to manage neutrality; Diversity, globalization, new technologies, and employee engagement; When leaders should facilitate and when others should do it; Sharing facilitation with others; This new edition also includes meeting design template, surveys, and questionnaires. -- Provided by publisher.